2020
DOI: 10.2217/cer-2019-0136
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of GP40061 compared with originator insulin glargine (Lantus ® ): a randomized open-label clinical trial

Abstract: Aim: To compare safety (immunogenicity) and efficacy of GP40061 insulin glargine (GP-Gla) and Lantus® (Sanofi glargine, Sa-Gla) in people with diabetes mellitus. Materials & methods: This randomized open-label, 26-week clinical trial enrolled 180 Type 1 diabetes mellitus patients (HbA1c 6.5–12.0%), randomized 1:1 to once daily GP-Gla (n = 90) or Sa-Gla (n = 90). The primary end point was immune response at 26th week. Results: The frequency of immune response was similar in GP-Gla and Sa-Gla (p = 1.000). Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…In addition, the safety results of Yamada et al and our study in hypoglycemia and severe hypoglycemia are 0.99 (95% CI 0.96 to 1.03) versus 0.96 (95% CI 0.85 to 1.09) and 1.09 (95% CI 0.80 to 1.47) versus 1.06 (95% CI 0.85 to 1.31), respectively. This study includes newly RCTs [ 25 , 28 30 ], pooled more comprehensive evidence in both long−/short acting insulin biologics, reports consistent outcomes than the previous study. However, our study grouped the studies with corrections combined with hypoglycemic drugs, and the results of the study were found to be similar (change of HbA1C at weeks 26, the MD were 0.03; 95% CI − 0.02 to 0.07, p = 0.28).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the safety results of Yamada et al and our study in hypoglycemia and severe hypoglycemia are 0.99 (95% CI 0.96 to 1.03) versus 0.96 (95% CI 0.85 to 1.09) and 1.09 (95% CI 0.80 to 1.47) versus 1.06 (95% CI 0.85 to 1.31), respectively. This study includes newly RCTs [ 25 , 28 30 ], pooled more comprehensive evidence in both long−/short acting insulin biologics, reports consistent outcomes than the previous study. However, our study grouped the studies with corrections combined with hypoglycemic drugs, and the results of the study were found to be similar (change of HbA1C at weeks 26, the MD were 0.03; 95% CI − 0.02 to 0.07, p = 0.28).…”
Section: Discussionmentioning
confidence: 83%
“…The question remains whether or not such a study includes all relevant patient groups for a sufficient period of time. A recent study performed in Russia with a BioIns of insulin glargine showed no differences in the immune response (or glycemic control) (24). Also, an in vitro evaluation of the immunogenic properties of a BioIns of insulin lispro showed no differences to both U.S.-and EUapproved Humalog based on a side-by-side biological similarity assessment (25).…”
Section: Immunogenicitymentioning
confidence: 93%
“…Participants from INSTRIDE 1 who completed 52 weeks of reference insulin glargine treatment were randomized 1:1 to the reference sequence (n = 63; insulin glargine for 36 weeks) or to the treatment-switching sequence (n = 64; MYL-1501D [weeks 0-12], insulin glargine [weeks [12][13][14][15][16][17][18][19][20][21][22][23][24], MYL-1501D [weeks [24][25][26][27][28][29][30][31][32][33][34][35][36]). The primary efficacy endpoint used to show equivalence between the two treatment sequences was a change in HbA1c from baseline to week 36.…”
Section: Methodsmentioning
confidence: 99%
“…Средняя концентрация АИА к концу исследования составила 4,32 ± 7,12 ИЕД/л в группе инсулина РинГлар ® и 5,33 ± 12,11 ИЕД/л без достоверной динамики по сравнению с исходными результатами. Снижение HbA1c в группе РинГлар ® составило -0,66%, в группе оригинального инсулина гларгина -0,77%, разница была недостоверной (р = 0,326) [29].…”
Section: Endocrinologyunclassified